Towards decarbonization goals: A Pathway to a sustainable future - Aditya Kolakoti; Muji Setiyo (Mechanical Engineering for Society and Industry, 2024)
Nature operates on a delicate balance of give and take. However, in the name of development, human activities have disrupted this balance by polluting ecosystems and releasing excessive greenhouse gases into the atmosphere. As a result, global temperatures are reaching unprecedented levels, leading to abrupt climatic changes that pose a significant threat to humanity. Immediate and collective action is essential to ensure the survival of future generations. The adoption of Decarbonization goals offers a promising pathway to mitigate greenhouse gas emissions and reduce the pollution burden on Earth, aiming for substantial progress by 2030.